Memorias del Congreso Internacional: América Latina y los Cien Años del Comienzo de la Primera Guerra Mundial (1914-2014) (2014)
Memorias del Congreso Internacional: América Latina y los Cien Años del Comienzo de la Primera Guerra Mundial (1914-2014)